STRATEGI PENGEMBANGAN KELEMBAGAAN KELOMPOK TANI PENGOLAH ROSELA DALAM MENGHADAPI PASAR BEBAS - CHARINA, ANNE (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2016)
Target of this research is to know and elaborate: Activity of rosela agroindustries in Lembang and also make correct strategy to develop rosela agroindustries in Lembang. The method of this research used by case study. Data which used in this research is primary and secunder data. Primary data obtained with direct interview technique to responden, the secunder obtained from various institution which related to this research. Data analysed descriptively, is and also used by Analysis of SWOT to get correct strategy in development ofÂ agroindustri rosela in Lembang.The result of this research are: the problem to develop of rosela agroindustri in Lembang in general for example is: lack of availability of Human Resource, lack of promotion and lack of support of medium and also institute. In consequence, strategy in development of rosela agroindustri in Lembang have to convergent local potency and strength and also orient market. Needed innovation and creativity to be tidy and market products of rosela sold authenticity, specification and local by rosela in Lembang.Keywords : Rosela, Agroindustries, Farmers, Free Trade Area